Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Prognostic factors and predictive modeling of in-hospital mortality among MDRO-positive inpatients: a retrospective cohort and GBD MICROBE study - Fan Jiang; Jian Li; Yahan Li; Yaping Yao; Ke Liu; Wei Dai; Hui Du (Antonie van Leeuwenhoek, 2026)

Numerical study on the icing hazard zone of engine intake components under anti-icing conditions - Shuliang Jing; Yaping Hu; Jing Xu; Yuetao Jiang; Weiliang Zheng; Yaxin Du (Cold Regions Science and Technology, 2026)

Dynamics of positive leader branching in long air gaps: A statistical exploration - Lili Guo; Xiangen Zhao; Xiankang Wang; Xiaopeng Liu; Yao Yao; Yaping Du; Junjia He (Atmospheric Research, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

Fabric-based composite membrane for simultaneous emulsion separation and self-powered real-time monitoring - Chengcheng Li; Chengjian Yao; Keru Hou; Jie Wang; Peibo Du; Jinping Zhang; Yinjie Chen; Xing Su; Yaping Zhao; Zaisheng Cai (Journal of Hazardous Materials, 2025)

Screening of siderophore-producing bacteria isolated from marine environments - Xiang Zeng; Guangyu Li; Yaping Du; Tong Yu; Qiliang Lai; Liping Wang; Zongze Shao (Acta Oceanologica Sinica, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Plasma-catalytic reforming of CO2–CH4 over nickel-based catalysts: Catalyst design, plasma activation, and comparison of different catalytic systems - Tian Chang; Xuanchen Chang; Zuotong Zhao; Chuanlong Ma; Xiangen Zhao; Yaping Du; Antonio Otavio T. Patrocinio; Anton Nikiforov; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

Multifunctional bilayer electrocatalytic membrane with high permeability and antifouling property for efficient removal of dye from water - Yuan Zhu; Gege Zhao; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Yating Ji; Zaisheng Cai; Yaping Zhao (Journal of Water Process Engineering, 2025)

Multi-protection durable unidirectional water-transport fabric with personalized moisture and thermal management - Gege Zhao; Yuan Zhu; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Zaisheng Cai; Yaping Zhao (Chemical Engineering Journal, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Release of bound phenol from Rosa roxburghii pomace via solid-state fermentation with Trichoderma viride: Mechanisms of change - Yanli Wang; Yaping Wang; Xiaoli Zhou; Bin Du; Yan Chen (Food Bioscience, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Role of Enterococcus mundtii in gut of the tomato leaf miner (Tuta absoluta) to detoxification of Chlorantraniliprole - Yao Chen; Yaping Chen; Yibo Zhang; Zhongxiang Sun; Yahong Li; Jiasheng Ding; Guifen Zhang; Ewei Du; Xiaoyan Zi; Chaoxin Tian; Wenyuan Zhao; Furong Gui (Pesticide Biochemistry and Physiology, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Micro-mechanism of the effect of multi-component gas injection on methane recovery - Huan Zhang; Wenfei Tao; Xiangyang Zhang; Hongbao Zhao; Shuangli Du; Chuang Song; Yaping lv; Haonan Chai; Mingyi Wang (Journal of Environmental Chemical Engineering, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

One-step preparation of magnetic N-doped sodium alginate–based porous carbon and efficient adsorption of bisphenol A - Yaping Xie; Guoxing Du; Jiaju Pang; Linghan Kong; Linguo Lu (Environmental Science and Pollution Research, 2023)

Distribution of benthic macrofaunal communities in intertidal flat under hydrodynamic influence: a case study of Jiangsu coast, East China - Longhui Zhang; Dezhi Chen; Shu Gao; Yaping Wang; Benwei Shi; Yongfen Du (Journal of Oceanology and Limnology, 2023)

Research on synthesis and property of nano-textured Sc2O3-MgO efficient antibacterial agents - Ying Wang; Yanjing Liu; Xiyue Li; Yuezhou Liu; Fuming Wang; Yaping Huang; Bing Du; Yongfang Qian; Lihua Lv (JBIC Journal of Biological Inorganic Chemistry, 2023)

The behavior of REEs indicates the dolomite petrogenesis and a unique dolomitization model of the Middle Permian Qixia formation in Northwest Sichuan Basin, China - Shengyang Xie; Xingzhi Wang; Bo Li; Long Wen; Liang Xu; Yao Du; Lin Xie; Yong Li; Yaping Wang; Yawen Li (Carbonates and Evaporites, 2022)

The Potential of Kelp Saccharina japonica in Shielding Pacific Oyster Crassostrea gigas From Elevated Seawater pCO2 Stress - Zengjie Jiang; Weiwei Jiang; Samuel P. S. Rastrick; Xiaoqin Wang; Jinghui Fang; Meirong Du; Yaping Gao; Yuze Mao; Øivind Strand; Jianguang Fang (Frontiers in Marine Science, 2022)
Ocean acidification (OA) caused by elevated atmospheric CO 2 concentration is predicted to have negative impacts on marine bivalves in aquaculture. However, to date, most of our knowledge is derived from short-term laboratory-based experiments, which are difficult to scale to real-world production. Therefore, field experiments, such as this study, are critical for improving ecological relevance. Due to the ability of seaweed to absorb dissolved carbon dioxide from the surrounding seawater through photosynthesis, seaweed has gained theoretical attention as a potential partner of bivalves in integrated aquaculture to help mitigate the adverse effects of OA. Consequently, this study investigates the impact of elevated p CO 2 on the physiological responses of the Pacific oyster Crassostrea gigas in the presence and absence of kelp ( Saccharina japonica ) using in situ mesocosms. For 30 days, mesocosms were exposed to six treatments, consisting of two p CO 2 treatments (500 and 900 μatm) combined with three biotic treatments (oyster alone, kelp alone, and integrated kelp and oyster aquaculture). Results showed that the clearance rate (CR) and scope for growth (SfG) of C. gigas were significantly reduced by elevated p CO 2 , whereas respiration rates (MO 2 ) and ammonium excretion rates (ER) were significantly increased. However, food absorption efficiency (AE) was not significantly affected by elevated p CO 2 . The presence of S. japonica changed the daytime pH NBS of experimental units by ~0.16 units in the elevated p CO 2 treatment. As a consequence, CR and SfG significantly increased and MO 2 and ER decreased compared to C. gigas exposed to elevated p CO 2 without S. japonica. These findings indicate that the presence of S. japonica in integrated aquaculture may help shield C. gigas from the negative effects of elevated seawater p CO 2 .

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Assessing the effects of oyster/kelp weight ratio on water column properties: an experimental IMTA study at Sanggou Bay, China - Jinghui Fang; Jianguang Fang; Qionglin Chen; Yuze Mao; Zengjie Jiang; Meirong Du; Yaping Gao; Fan Lin (Journal of Oceanology and Limnology, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Nonlabens xiamenensis sp. nov., isolated from coastal seawater - Zhaobin Huang; Yaping Du; Qiliang Lai; Zongze Shao (Antonie van Leeuwenhoek, 2019)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Photosynthetic and metabolic responses of eelgrass Zostera marina L. to short-term high-temperature exposure - Yaping Gao; Zengjie Jiang; Meirong Du; Jinghui Fang; Weiwei Jiang; Jianguang Fang (Journal of Oceanology and Limnology, 2019)

Selectivity of Perinereis aibuhitensis (Polychaeta, Nereididae) feeding on sediment - Jinghui Fang; Zengjie Jiang; Jianguang Fang; Bin Kang; Yaping Gao; Meirong Du (Marine Biology Research, 2018)

Chemical characterization of fractions of dissolved humic substances from a marginal sea—a case from the Southern Yellow Sea - Yaoling Zhang; Keli Yang; Jinzhou Du; Fenfen Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2018)

Size fraction of phytoplankton and the contribution of natural plankton to the carbon source of Zhikong scallop Chlamys farreri in mariculture ecosystem of the Sanggou Bay - Zengjie Jiang; Meirong Du; Jinghui Fang; Yaping Gao; Jiaqi Li; Li Zhao; Jianguang Fang (Acta Oceanologica Sinica, 2017)

HUCMNCs protect vascular endothelium and prevent ISR after endovascular interventional therapy for vascular diseases in T2DM rabbits - Haixia Ding; Tong Zhang; Yaping Du; Bei Liu; Yueqin Liu; Fujun Wang (Molecular and Cellular Biochemistry, 2017)

Applicability of Perinereis aibuhitensis Grube for fish waste removal from fish cages in Sanggou Bay, P. R. China - Jinghui Fang; Zengjie Jiang; Henrice M. Jansen; Fawen Hu; Jianguang Fang; Yi Liu; Yaping Gao; Meirong Du (Journal of Ocean University of China, 2017)

Environmental remediation potential of Perinereis aibuhitensis (Polychaeta) based on the effects of temperature and feed types on its carbon and nitrogen budgets - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Meirong Du; Yi Liu; Yuze Mao; Yaping Gao; Jianguang Fang (Marine Biology Research, 2016)

Erratum to: Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Tolerance, oxygen consumption and ammonia excretion of Ophiopholis sarsii vadicola in different temperatures and salinities - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Xuewei Zhao; Xu Jiang; Meirong Du; Yaping Gao; Jianguang Fang (Journal of Ocean University of China, 2015)

Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Pseudooceanicola atlanticus gen. nov. sp. nov., isolated from surface seawater of the Atlantic Ocean and reclassification of Oceanicola batsensis, Oceanicola marinus, Oceanicola nitratireducens, Oceanicola nanhaiensis, Oceanicola antarcticus and Oceanicola flagellatus, as Pseudooceanicola batsensis comb. nov., Pseudooceanicola marinus comb. nov., Pseudooceanicola nitratireducens comb. nov., Pseudooceanicola nanhaiensis comb. nov., Pseudooceanicola antarcticus comb. nov., and Pseudooceanicola flagellatus comb. nov. - Qiliang Lai; Guizhen Li; Xiupian Liu; Yaping Du; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Emcibacter nanhaiensis gen. nov. sp. nov., isolated from sediment of the South China Sea - Xiupian Liu; Guangyu Li; Qiliang Lai; Fengqin Sun; Yaping Du; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Idiomarina atlantica sp. nov., a marine bacterium isolated from the deep sea sediment of the North Atlantic Ocean - Juan Du; Qiliang Lai; Yang Liu; Yaping Du; Xiupian Liu; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Actibacterium atlanticum sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Yaping Du; Xiupian Liu; Guangyu Li; Yunbiao Xie; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Aquimarina atlantica sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Xiupian Liu; Yunbiao Xie; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Erratum to: Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2013)

Growth and loss of mariculture kelp Saccharina japonica in Sungo Bay, China - Jihong Zhang; Jianguang Fang; Wei Wang; Meirong Du; Yaping Gao; Mingliang Zhang (Journal of Applied Phycology, 2012)